Effect of the Winter Wheat Cheyenne 5A Substituted Chromosome on Dynamics of Abscisic Acid and Cytokinins in Freezing-Sensitive Chinese Spring Genetic Background - Kalapos, Balázs; Novák, Aliz; Dobrev, Petre; Vítámvás, Pavel; Marincs, Ferenc; Galiba, Gábor; Vanková, Radomira (Frontiers in Plant Science, 2017)
The effect of short- and long-term cold treatment on the abscisic acid (ABA) and cytokinin (CK) metabolism, and their main biosynthesis and signaling related genes were investigated in freezing-sensitive and freezing-tolerant wheat genotypes. Varieties Cheyenne and Chinese Spring substituted with the 5A Cheyenne chromosome, which represented freezing-tolerant genotypes, were compared with the freezing-sensitive Chinese Spring. Hormone levels and gene expression data indicated that the short- and long-term cold treatments are associated with specific regulation of the accumulation of cold protective proteins and phytohormone levels, as well as the expression profiles of the hormone-related genes. The significant differences were observed between the genotypes, and between their leaf and crown tissues, too. The level of dehydrins, including WCS120 protein, and expression of WCS120 gene were considerably higher in the freezing tolerant genotypes after 21 days cold treatment. Expression of Cor14b and CBF14, cold responsive regulator genes, was increased by cold treatment in all genotypes, to higher extent in freezing-tolerant genotypes. Cluster analysis revealed that the tolerant genotypes had a similar response to cold treatment, regarding expression of the ABA and CK metabolic genes, as well as hormone levels in leaves. As far as hormone levels in crowns are concerned, however, the strongly freezing-tolerant Cheyenne variety clustered separately from the Chinese Spring and the substitution line, which were more similar to each other after both one and 21 days of cold treatment than to Cheyenne. Based on these results we concluded that the 5A chromosome of wheat might have both a direct and an indirect impact on the phytohormone dependent cold-induced freezing tolerance. Based on the gene expression data, novel genetic markers could be developed, which may be used to determine the freezing tolerance level in a wide range of wheat varieties.